Fabrication of ZnS with necklace-like hierarchical structure-decorated graphene and its photocatalytic performance. (April 2018) - Zeng, Bin; Zeng, Wujun; Liu, Wanfeng; Jin, Can
Abstract: In this study, we used a microwave reaction to fabricate necklace-like ZnS with a hierarchical structure dispersed on the surface of graphene sheets (ZnS NHS-G). The structure and properties of the ZnS NHS-G were characterized based on X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, photoluminescence spectroscopy, electrochemical impedance spectroscopy, and the photocurrent response. The results showed that a clear increase in the photocatalytic performance was achieved with ZnS NHS-G, which was attributed to the longer lifetime of the photogenerated electrons. Furthermore, the unique morphology of the necklace-like hierarchical structure enhanced its photocatalytic properties. Thus, this semiconductor may be used as an efficient photocatalyst in the future. Highlights: The graphene loaded necklace-like ZnS with a hierarchical structure was fabricated using a microwave reaction. Excellent photocatalytic performance.